MODELING AND VALIDATION OF SIX-BAR RACK AND PINION STEERING LINKAGE SYSTEM - Mohammad Nasir, Mohd Zakaria; Amir, Mohd Zubir; Hudha, Khisbullah; ABDULLAH, Mohd Azman; Hassan, Muhammad Zahir (2012)
A vehicle handling behavior is much influenced by the performance of steering system and its mechanism. Steering linkage play a very important role in maneuvering of a vehicle. In this paper, a planar six-bar rack and pinion steering linkage is modeled in MATLAB SIMULINK to study the relationship between steering wheel angle and tire angle. A set of kinematic relations of steering system is used to analyze the kinematics of a planar linkage. The steering system consists of rack and pinion, tie rod end, tire and steering wheel column are modeled in MATLAB SIMULINK environment based on kinematic model equations is presented. The model is then validated using Hardware-in-the-loop simulations (HILS) consists of LVDT and rotary encoder sensors installed in actual steering system for data measurement at various steering angle. Results from simulation model has been developed demonstrates a linear pattern occurred from maximum lock-to-lock steering wheel angle and it’s closely follow the trend through HILS experiment.